Pengetahuan Anemia Ibu Hamil di Kelurahan Kuto Batu - Novianty; Amelia Prahastuti; Putri Sinta Maharani; Nessy Iqmadhea (jurnal kesehatan terapan sains dan teknologi, 2023)
Pregnancy are a special condition that requires more nutritional needs compared to other conditions in the life cycle. Therefore pregnancy get a number of additional macro and micro nutrients during pregnancy. Mother's nutritional needs that are not met will cause various nutritional problems including anemia. Anemia in pregnancy can cause health and nutritional problems not only for the mother but also for the fetus. The research was conducted in Kuto Batu Palembang Village in August 2022. The subjects of the study were 26 pregnant in trimesters 1, 2 and 3. The results showed that most of the mothers, namely 85%, had insufficient knowledge of anemia. Lack of knowledge can influence mother's behavior related to anemia prevention. Mothers who have less knowledge regarding anemia will have difficulty choosing and consuming foods high in iron.